The effectiveness of the PBL learning model on students' problem-solving abilities in the subject of jama qasar prayers - Rahayu, Ayu Puji; Murharyana, Murharyana; Baari, Rosmalati Muthiatil; Ibupoto, Mukhtiar Hussain (At- Ta'lim : Jurnal Pendidikan, 2024)
Students' problem-solving abilities still need to be considered higher. Therefore, variations are needed in learning models that can increase critical thinking and independence in learning. This research aims to test the effectiveness of the PBL learning model in improving students' problem-solving abilities in the subject of Jama Qasar prayers. This study uses a quasi-experiment to compare the pretest and posttest scores of two data groups. The N-Gain test was carried out to analyze the increase in the effectiveness of the treatment given, especially in comparing pretest and posttest data between two groups. Apart from that, hypothesis testing uses the Coefficients test from inferential analysis of linear regression tests. Meanwhile, the subjects of this research were class VII students at Yunior High School Darul Falah, West Bandung. This study did not use randomization, and the subjects were selected based on class availability. The research results show that the PBL learning model can significantly improve students' problem-solving abilities.